2012
DOI: 10.5539/ass.v8n6p184
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Relationships and Communication among the Rural Aged in Malaysia

Abstract: In Malaysia the family has been the main institution caring for the aged. However, the processes of development, directly or indirectly, have impacted the size, functions and structure of the family unit, which subsequently impacted the family intergenerational relationships and communication. This study is about the intergenerational relationships and communication specifically among the rural aged with their family members. The main objective is to further understand the relationship of the aged with those a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…In another local study, Aziz and Yusooff (2012) revealed that adult children in rural areas coreside with their own parents as they need their parents to help manage the household, give advice to and supervise growing grandchildren, look after the grandchildren when parents away at work, and to ensure family harmony. Elders in multigenerational families in rural areas have positive intergenerational relationships with adult children and grandchildren (Aziz & Yusooff, 2012), while another study showed that some elderly residing in rural areas refused to stay with adult children and grandchildren as they think adult children and grandchildren are too noisy or with different daily routine or habits (Evans et al., 2018). Although these changing family structures and urban migration patterns are increasingly common in rural areas worldwide, the experiences of rural families with different ethnic compositions and living arrangements in Malaysia have been neglected in psychological research.…”
Section: Multicultural and Multigenerational Families In Malaysiamentioning
confidence: 99%
See 2 more Smart Citations
“…In another local study, Aziz and Yusooff (2012) revealed that adult children in rural areas coreside with their own parents as they need their parents to help manage the household, give advice to and supervise growing grandchildren, look after the grandchildren when parents away at work, and to ensure family harmony. Elders in multigenerational families in rural areas have positive intergenerational relationships with adult children and grandchildren (Aziz & Yusooff, 2012), while another study showed that some elderly residing in rural areas refused to stay with adult children and grandchildren as they think adult children and grandchildren are too noisy or with different daily routine or habits (Evans et al., 2018). Although these changing family structures and urban migration patterns are increasingly common in rural areas worldwide, the experiences of rural families with different ethnic compositions and living arrangements in Malaysia have been neglected in psychological research.…”
Section: Multicultural and Multigenerational Families In Malaysiamentioning
confidence: 99%
“…Taking into consideration the potential variations in family dynamics across different living arrangements, it is crucial to investigate intergenerational bonding and outcomes of grandchildren's social skill development in the absence of parents within skipped generation families, compared to three‐generation families where the parents are present. However, the majority of recent local research has been descriptive, focusing on the trends of increasing skipped generation families or general types of grandparental childcare patterns (e.g., Aziz & Yusooff, 2012; Noor & Mahudin, 2016). There are limited empirical studies comparing the associations between GP–GC interactions and the social skill development of grandchildren in skipped generation versus three‐generation families.…”
Section: Multicultural and Multigenerational Families In Malaysiamentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, preference may be given to those who can accommodate and adapt by placing personal goals aside in order to seek a path that benefits the entire family system. Malaysian culture often defines the family as inclusive of extended family and multiple generations (Abdul Aziz & Yusooff, 2012).…”
Section: Group Presentations Based On Course Readings and Reflective mentioning
confidence: 99%
“…Elders tend to be highly honored and valued within Malaysian family structures, which may be related to filial piety. Filial piety encourages veneration and respect for one’s elders and ancestors (Abdul Aziz & Yusooff, 2012). It is not uncommon for multiple generations of extended family to cohabitate and share household responsibilities.…”
Section: Group Presentations Based On Course Readings and Reflective mentioning
confidence: 99%